Characterization of Gelatin Profile of Chicken Broiler (Gallus domestica) Bone Using SDS-PAGE Electrophoresis - Yuliani, Dewi; Awalsasi, Dhienda Risa; Jannah, Akyunul (ALCHEMY, 2019)
Gelatin, a proteinaceous additive, is obtained from hydrolysis of collagen in the bone, hide and skin of animals. As natural product, gelatin has been applied in many industries with various functions. This study attempt to characterize gelatin profile of broiler chicken (Gallus domestica) using SDS-PAGE electrophoresis. The chicken bone was pretreated using a strong base, sodium hydroxide, producing type B gelatin. The gelatin was purified through precipitation using the variation of ammonium sulfate concentrations (40-70%) and dialysis using cellophane membrane. The purified gelatin was characterized through SDS-PAGE electrophoresis. Based on electrophoresis visualization, reduction of band intensity by ammonium sulfate 40% showed removal of small peptide fragments. The remained gelatin showed two major bands, α-chains and a β-chain with the respective molecular weight of ~135 and ~245 kDa. The protein content of the unpurified gelatin (E1) was 71.65±0.60 mg/L.  The purified E1 gelatins by 40-70% of ammonium sulfate addition contained 61.42±3.90, 60.45±1.36, 59.89±0.24, and 55.32±1.05 mg/L of protein concentration, respectively. Keywords: chicken bone, gelatin profile, protein electrophoresis